THE USE OF AI TECHNOLOGY IN LANGUAGE LEARNING - Shevchenko, Olga (European Science, 2024)
This paper explores some innovative methods of learning a foreign language using Artificial intelligence (AI) technology. Numerous researchers and educators continue to study the impact of AI on future language learning and teaching. The gradual integrat